Wound healing and anti-inflammatory activity of extract of Ficus racemosa linn. bark in albino rats - Mehta, Dimple S.; Kataria, Bhaven C.; Chhaiya, Sunita B. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: F. racemosa is an indigenous plant having anti-secretory, anti-diabetic, anti-ulcer etc. properties. It is used widely in the ayurvedic medicines. Methods: The experimental models of wound and inflammation were used to assess the wound healing and anti-inflammatory properties of F. racemosa. The significance of differences was analyzed using students’ ‘t’ test. Results: In the strength of 10% local application it could apparently enhanced the process of healing. At the dose of 20 mg/100 gm intraperitoneally it could show inhibition of carageenan induced acute inflammation at 3rd, 5th and 7th hour and at the dose of 30 mg/100 gm intraperitoneally, formalin induced subacute inflammation was inhibited till 4th day. The results were found statistically significant. Conclusions: Aqueous extract of F. racemosa has got wound healing and anti-inflammatory activity. It is likely that the duration of action may be shorter.